'India @75: Religion and Citizenship in India'. (June 2022) - Khosla, Madhav; Vaishnav, Milan
As India celebrates 75 years of independence, fresh questions are being raised about who is an Indian. This essay introduces a special section of Studies in Indian Politics which puts forward answers to this question considering recent tectonic changes in India's political climate and party system. We outline how religion is being increasingly adopted as a filter through which citizenship is decided—both in formal, legal terms as well as in informal terms. The special section delves deeper into this terrain, exploring several critical themes: de jure changes to India's citizenship regime, the relationship between Hindu nationalism and liberal democracy, the judiciary's role in adjudicating religious disputes, the Muslim community's response to recent policy shifts and the changing nature of electoral coalition building. Taken together, the articles in this section represent a signal contribution to ongoing debates in India—and elsewhere—on democracy, nationalism and inclusion.